Internalisasi Sikap Toleransi Melalui Pembelajaran PAI di Sekolah Indonesia Den Haag - Moh Miftakhul Huda; Riza Zahriyal Falah; Nailna Amanina; M. Ahsanul Mubarok (Edification Journal : Pendidikan Agama Islam, 2021)
This study aims to describe the method of introducing tolerance through Islamic education learning and its stages at the Indonesian School in The Hague. The background of this research stems from the researcher's interest in finding out how educators at SIDH overcome various problems such as promiscuity, bullying, the position of minorities based on citizenship and religion, and complex cultural and cultural differences. This research uses qualitative research methods with a descriptive approach. The subjects in this study were teachers and principals of SIDH. The data collection technique is done by interview and documentation technique. The results of the study were the methods used by educators in the introduction of tolerant attitudes including exemplary, guidance, and habituation methods. Its implementation is in classical and online learning activities (in network) and also in supporting activities for Islamic education. The stages include the stages of information, appreciation, application,